(untitled) (Eurasian Journal of Ecology, 2020)
Due to the serious danger to the environment and human health, aromatic hydrocarbons have recently become the subject of extensive research. They can easily spread in soils and groundwater as a result of the oil production process, leaking tanks and problems encountered during transportation over long distances. Therefore, their removal is one of the most important environmental problems. Biological methods of purification of the natural environment are the safest, most effective and less expensive in comparison with the methods of chemical and physical purification. Currently, most efforts are aimed at finding bacterial communities capable of mineralizing pollutants into less harmful, non-hazardous compounds. Moreover, the use of consortia can further increase the efficiency of decomposition of hydrocarbons, since they have multiple metabolic capabilities. Earlier, we isolated hydrocarbon-oxidizing microorganisms capable of oxidizing o-xylene from oil-contaminated soils of Western Kazakhstan. The aim of this work was the creation of bacterial consortia, and study the efficiency of degradation of xylene isomer mixture. By the method of semi-continuous cultivation, variants of strains with increased oxidative potential were obtained. Their ability to grow on m- and p-xylene was tested. Based on selected active strains of hydrocarbon-oxidizing bacteria there have been created consortia which effectively degrade xylene isomers. After 24 h of cultivation of xylene oxidizing consortia, the residual content of o-xylene in the medium was 6.1-12.7%, m-xylene – 4.5-10.2%, p-xylene – 10.2-20.2%. The highest activity was shown by the consortium 8 (B. megaterium 1/1 an, B. thuringiensis 2/4 fl, B. tropicus 2/6 fl, B. megaterium P1-fl1-5), which utilized 89.8-95.5% test substrates. Key words: biodegradation, hydrocarbon-oxidizing bacteria, consortium, xylene isomers.